Ultrasound regulated flexible protein materials: Fabrication, structure and physical-biological properties - Cai, Bowen; Gu, Hanling; Wang, Fang; Printon, Kyle; Gu, Zhenggui; Hu, Xiao (Ultrasonics sonochemistry, 2021)
[Display omitted] •A novel ultrasound technique to fabricate flexible protein materials.•Protein structure and properties can be tuned by varying ultrasound power and time.•Biological responses can be controlled by ultrasound-generated protein materials.•Ultrasound technique is a high efficient and easy to operate without any chemical procedures.•Mechanism of ultrasonic effects on protein differents properties are revealed. Ultrasound can be used in the biomaterial field due to its high efficiency, easy operation, no chemical treatment, repeatability and high level of control. In this work, we demonstrated that ultrasound is able to quickly regulate protein structure at the solution assembly stage to obtain the designed properties of protein-based materials. Silk fibroin proteins dissolved in a formic acid-CaCl2 solution system were treated in an ultrasound with varying times and powers. By altering these variables, the silks physical properties and structures can be fine-tuned and the results were investigated with Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), dynamic mechanical analysis (DMA), gas permeability and water contact angle measurements. Ultrasonic treatment aids the interactions between the calcium ions and silk molecular chains which leads to increased amounts of intermolecular β-sheets and α-helix. This unique structural change caused the silk film to be highly insoluble in water while also inducing a hydrophilic swelling property. The ultrasound-regulated silk materials also showed higher thermal stability, better biocompatibility and breathability, and favorable mechanical strength and flexibility. It was also possible to tune the enzymatic degradation rate and biological response (cell growth and proliferation) of protein materials by changing ultrasound parameters. This study provides a unique physical and non-contact material processing method for the wide applications of protein-based biomaterials.